Vive l’agrobiodiversité ! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Incentive measures for sustainable use and conservation of agrobiodiversity. Experience and lessons from southern Africa. Actes de l’atelier tenu à Lusaka, Zambie, du 11 au 14 septembre 2001. Rédigé par by C. Almekinders, SPGRC — GTZ — IPGRI — CTD